Marine Protection Induces Morphological Variation in the California Moray, Gymnothorax mordax. (12th June 2020) - Mehta, Rita S; Dale, Katherine E; Higgins, Benjamin A
Synopsis: The effectiveness of marine protected areas (MPAs) on the general health and conservation of species, habitats, and community interactions is of great interest to researchers, managers, and recreationalists. However, the ecological and behavioral diversity of vertebrate predators of southern California kelp forests limits our ability to make general conclusions about MPA effectiveness across a variety of species. Identifying and studying species with extreme feeding habits or prey-capture strategies may offer greater insight into predator–prey relationships and reveal the trophic importance of an animal in the larger community. Moray eels (family Muraenidae) have been shown to have morphological and behavioral adaptations that allow them to consume large prey whole, identifying them as important predators. From 2015 to 2018, we studied the health and feeding behavior of a long-lived, elusive, and benthic kelp forest predator, the California moray eel ( Gymnothorax mordax ). We trapped eels inside and outside of Blue Cavern Onshore State Marine Conservation Area, an MPA on the northwest side of Santa Catalina Island, CA which prohibits the take of any species. Over 4 years, we captured 1736 eels. Overall, we found that morays were longer, older, heavier, had higher body condition, and were found in greater abundance within the MPA. Although fish comprised the majority of their summer diet, morays outside of the MPA were consuming a more diverse set of fish, while kelp bass comprised more than half of the diet for morays inhabiting the MPA. Additionally, we found that morays within the MPA had larger relative vertical gape distances (VGDs) and narrower heads. Our recapture data support the high site fidelity of morays, indicating that their diet and morphology are influenced by their local community. While the majority of morays are thriving in the MPA, as suggested by their robust sizes and longevity, high abundance appears to result in higher frequencies of cannibalism, the presence of an undescribed disease, and lower growth rates. Our results suggest that the MPA affects the life history of morays and may select for an alternative feeding strategy in which eels develop larger VGDs, smaller adductor muscles, and a specialized diet which is presumably influenced by the local environment. In addition, observations of cannibalistic behavior and species-specific disease provide us with important insight into natural factors that may still regulate populations removed from anthropogenic disturbances such as fishing.